Austenitic stainless steel plates and their manufacturing methods, as well as leaf springs

CN117999375BActive Publication Date: 2026-10-27NIPPON STEEL STAINLESS STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280064925.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-06
Filing Date
2022-10-20
Publication Date
2026-10-27
Estimated Expiration
2042-10-20

AI Technical Summary

Benefits of technology

[0028]根据本发明,能够提供一种即使厚度减薄也具有高强度的、且疲劳特性优异的奥氏体系不锈钢板及其制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004759048140000151
    Figure BDA0004759048140000151
  • Figure BDA0004759048140000161
    Figure BDA0004759048140000161
  • Figure BDA0004759048140000181
    Figure BDA0004759048140000181
Patent Text Reader

Abstract

This invention provides an austenitic stainless steel plate, the composition of which, by mass, contains C: 0.04-0.11%, Si: 2.0-3.5%, Mn: less than 1.50%, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: less than 1.00%, N: 0.03-0.15%, O: less than 0.0050%, with the remainder being Fe and impurities, and having Md represented by the following formula (1). 30 The value is -30 to 0℃, Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo(1) (where the element symbols represent the content (mass%) of each element). Austenitic stainless steel plates have a metallic structure with a work-induced martensite phase content of more than 30.0% by volume and a thickness of less than 0.15mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to austenitic stainless steel plates, methods for manufacturing the same, and leaf springs. Background Technology

[0002] With the miniaturization and increasing performance of communication devices such as smartphones and precision equipment such as personal computers, there has been ongoing research into thinner and lighter structural and functional components used in these devices. Therefore, the materials used in these components require high strength even with reduced thickness. In particular, in foldable smartphones, leaf springs are used in the backplate that supports the bending function of the LCD screen. Components such as leaf springs, which withstand repeated bending, must be able to withstand fatigue characteristics caused by repeated bending.

[0003] As a material used in components such as leaf springs, Patent Document 1 discloses an austenitic stainless steel sheet, which is manufactured by cold working the stainless steel at a low temperature of -20°C to 70°C with a reduction rate of 30% to 70%, causing a portion of its austenitic phase to transform into work-induced martensite, followed by aging treatment at 300% to 650°C for 0.1% to 90 minutes. The stainless steel contains, by mass%, less than 0.10% C, more than 1.0% to 4.0% Si, less than 2.0% Mn. Ni: 4.0%–10.0%, Cr: 12.0%–18.0%, N: less than 0.15%, and contains these elements in a manner where C+N≥0.10%, and the value of Md(N) based on the formula Md(N)=580-520C-2Si-16Mn-16Cr-23Ni-300N-26Cu-10Mo is in the range of 20–70. The remainder contains Fe and impurities that are inevitably mixed in during manufacturing, and exhibits a metastable austenitic phase in the solution-treated state.

[0004] Furthermore, as a material with excellent fatigue properties, Patent Document 2 proposes an austenitic stainless steel plate, which, by mass percent, contains C: less than 0.15%, Si: 1.0–4.0%, Mn: less than 5.0%, Ni: 4.0–10.0%, Cr: 12.0–18.0%, Cu: 0–3.5% (including no addition), Mo: 1.0–5.0%, and N: less than 0.15%, and satisfies C+N≥0.10% and Si+Mo≥3.5%, and is fixed A steel plate with Md(N) values ​​ranging from 20 to 100, defined as Md(N) = 580-520 × [%C] - 2 × [%Si] - 16 × [%Mn] - 16 × [%Cr] - 23 × [%Ni] - 300 × [%N] - 26 × [%Cu] - 10 × [%Mo], containing Fe and unavoidable impurity elements, and exhibiting precipitates with a maximum size of less than 0.5 μm, has a tensile strength of 1800 N / mm². 2 above.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 7-90372

[0008] Patent Document 2: Japanese Patent Application Publication No. 10-140294 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] The austenitic stainless steel sheets described in Patent Documents 1 and 2 cannot be said to have sufficient strength when the thickness is relatively thin (especially when the thickness is less than 0.15 mm).

[0011] The present invention was made to solve the problems mentioned above, and its purpose is to provide an austenitic stainless steel plate with high strength and excellent fatigue characteristics even with reduced thickness, and a method for manufacturing the same.

[0012] Furthermore, the present invention aims to provide a leaf spring that has high strength and long lifespan even with reduced thickness.

[0013] Methods for solving problems

[0014] The inventors conducted in-depth research and found that the above problems could be solved by controlling the composition and metal structure of austenitic stainless steel plates, thus completing this invention.

[0015] In other words, the present invention relates to an austenitic stainless steel plate, the composition of which, by mass, contains C: 0.04-0.11%, Si: 2.0-3.5%, Mn: less than 1.50%, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: less than 1.00%, N: 0.03-0.15%, O: less than 0.0050%, with the remainder containing Fe and impurities, and Md represented by the following formula (1). 30 The temperature range is -30 to 0℃, and the metal structure has a content of more than 30.0% by volume of processing-induced martensite phase and a thickness of less than 0.15 mm.

[0016] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)

[0017] In the formula, the element symbols represent the content (mass%) of each element.

[0018] Furthermore, the present invention relates to a method for manufacturing an austenitic stainless steel sheet, comprising the following steps:

[0019] The intermediate rolling annealing process involves sequentially cold rolling and annealing the hot-rolled annealed sheet, and repeating this step more than twice. The composition of the hot-rolled annealed sheet, based on mass, contains C: 0.04-0.11%, Si: 2.0-3.5%, Mn: less than 1.50%, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: less than 1.00%, N: 0.03-0.15%, O: less than 0.0050%, with the remainder containing Fe and impurities. Md is expressed by the following formula (1). 30 The value is -30 to 0℃.

[0020] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)

[0021] In the formula, the element symbols represent the content (mass%) of each element;

[0022] The temper rolling process involves temper rolling the cold-rolled annealed sheet obtained from the intermediate rolling annealing process at a rolling rate of 60% or more, thereby adjusting the thickness to below 0.15 mm; and

[0023] The aging process involves aging the tempered rolled plate obtained from the tempering rolling process according to the following formula (2), where the B value is between 11500 and 15000.

[0024] B = T(logt + 20) (2)

[0025] In the formula, T is temperature (K) and t is time (h).

[0026] In addition, the present invention relates to leaf springs comprising the aforementioned austenitic stainless steel plates.

[0027] Invention Effects

[0028] According to the present invention, an austenitic stainless steel plate with high strength and excellent fatigue properties even with reduced thickness and a method thereof can be provided.

[0029] Furthermore, according to the present invention, it is possible to provide a leaf spring that has high strength and long lifespan even with reduced thickness. Detailed Implementation

[0030] The embodiments of the present invention will now be described in detail. The present invention is not limited to the following embodiments. Without departing from the spirit of the present invention, appropriate changes and improvements can be made to the following embodiments based on the common knowledge of those skilled in the art, and all such modifications and improvements should be understood to fall within the scope of the present invention.

[0031] In addition, unless otherwise specified, the percentages of ingredients in this specification refer to mass.

[0032] The embodiments of the present invention relate to an austenitic stainless steel plate, which contains C: 0.04-0.11%, Si: 2.0-3.5%, Mn: less than 1.50%, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: less than 1.00%, N: 0.03-0.15%, O: less than 0.0050%, and the remainder contains Fe and impurities.

[0033] In this specification, the term "austenite system" refers to a metal whose microstructure at room temperature is primarily austenitic. Therefore, the "austenite system" includes a small amount of phases other than austenitic phases (such as ferrite and martensite).

[0034] Furthermore, the term "impurity" refers to components that may be introduced into the industrial production of austenitic stainless steel sheets due to various reasons related to raw materials such as ores and waste, as well as the manufacturing process. These components are permissible to a extent that they do not adversely affect the present invention. For example, unavoidable impurities that are difficult to remove, such as phosphorus (P) or sulfur (S), may also be included in this category.

[0035] In addition, regarding the content of each element in this specification, the phrase "containing less than xx%" means less than xx%, but contains an amount exceeding 0% (especially exceeding the impurity level).

[0036] Furthermore, the austenitic stainless steel sheet of the embodiments of the present invention may, as needed, further contain one or more of the following: Co: 0.05-0.50%, Al: less than 0.15%, V: 0.0001-0.5000%, Ti: 0.01-0.50%, B: 0.0001-0.0150%, Nb: 0.001-0.100%, Mg: 0.0001-0.0030%, Ca: 0.0003-0.0100%, Sn: 0.001-0.500%, Pb: 0.0001-0.0100%, W: 0.0001-0.5000%, Zr: 0.0001-0.1000%, and REM: 0.0001-0.3000%. Therefore, the austenitic stainless steel plate according to embodiments of the present invention can be expressed as having the following composition: containing C: 0.04-0.11%, Si: 2.0-3.5%, Mn: 1.50% or less, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: 1.00% or less, N: 0.03-0.15%, and O: 0.0050% or less, further containing an alloy selected from Co: 0.05-0.50%, Al: 0-0.15%, and V: 0.0001-0.500%. One or more of the following: 0%, Ti: 0.01-0.50%, B: 0.0001-0.0150%, Nb: 0.001-0.100%, Mg: 0.0001-0.0030%, Ca: 0.0003-0.0100%, Sn: 0.001-0.500%, Pb: 0.0001-0.0100%, W: 0.0001-0.5000%, Zr: 0.0001-0.1000%, and REM: 0.0001-0.3000%, with the remainder containing Fe and impurities.

[0037] Regarding the content of each element in this specification, the phrase "0 to xx%" means below xx%, but also includes the concept of 0% (excluding 0%).

[0038] The following is a detailed explanation of each component.

[0039] <C:0.04~0.11%>

[0040] C is an interstitial element, which contributes to high strength enhancement based on work hardening and aging treatment. In addition, C is an element that stabilizes the austenite phase, and is also effective for maintaining non-magnetic properties. However, if the C content is excessively high, it causes hardening and leads to reduced cold workability. Therefore, the upper limit of the C content can be set to 0.11%, preferably 0.10%, and more preferably 0.09%. On the other hand, from the viewpoint of refining cost, the lower limit of the C content can be set to 0.04%, preferably 0.05%, and more preferably 0.06%.

[0041] <Si: 2.0 to 3.5%>

[0042] Si is an element used as a deoxidizer for stainless steel in the steelmaking process. In addition, Si also has the effect of improving hardenability during aging treatment. However, since Si has a significant solid solution strengthening effect and acts to improve work hardenability by lowering stacking fault energy, an excessively high Si content will cause reduced cold workability. Therefore, the upper limit of the Si content can be set to 3.5%, preferably 3.3%, and more preferably 3.0%. On the other hand, from the viewpoint of ensuring the above-mentioned effects of Si, the lower limit of the Si content can be set to 2.0%, preferably 2.1%, and more preferably 2.2%.

[0043] <Mn: 1.50% or less>

[0044] Mn is an element that forms oxide-based inclusions (MnO). In addition, Mn is an element with low solid solution strengthening effect and forms austenite, and has the effect of suppressing work-induced martensitic transformation. Therefore, the upper limit of the Mn content can be set to 1.50%, preferably 1.40%, and more preferably 1.30%. On the other hand, the lower limit of the Mn content is not particularly limited, but is preferably set to 0.01%, more preferably 0.05%, and even more preferably 0.10%.

[0045] <Ni: 6.0 to 10.0%>

[0046] Ni is an element contained to obtain an austenite phase at high temperatures and room temperature. Ni is required to form a metastable austenite phase at room temperature and induce a martensite phase during cold rolling. If the Ni content is too low, a δ-ferrite phase forms at high temperatures, and a martensite phase forms during cooling to room temperature, making it impossible to exist in a single austenite phase. Therefore, the lower limit of the Ni content can be set to 6.0%, preferably 6.3%, and more preferably 6.5%. On the other hand, if the Ni content is too high, it is difficult to induce the martensite phase during cold rolling. Therefore, the upper limit of the Ni content can be set to 10.0%, preferably 9.5%, and more preferably 9.0%.

[0047] <Cr: 12.0 to 15.0%>

[0048] Cr is an element that improves the corrosion resistance of austenitic stainless steel sheets. From the viewpoint of ensuring corrosion resistance suitable for structural members and functional members (particularly leaf springs) and the like, the lower limit of the Cr content can be set to 12.0%, preferably 12.5%, and more preferably 13.0%. On the other hand, if the Cr content is too high, the cold workability deteriorates. Therefore, the upper limit of the Cr content can be set to 15.0%, preferably 14.8%, and more preferably 14.5%.

[0049] <Mo: 1.3 to 3.2%>

[0050] Mo is an effective element for improving the corrosion resistance of austenitic stainless steel sheets. In addition, Mo is also an effective element for suppressing the release of strain generated during cold rolling. In recent years, in consideration of use in structural members and functional members (particularly leaf springs) that require improved corrosion resistance and fatigue properties, the lower limit of the Mo content can be set to 1.3%, preferably 1.5%, and more preferably 1.7%. On the other hand, since Mo is a high-priced metal, an excessively high Mo content leads to an increase in manufacturing cost. In addition, a δ-ferrite phase and an α-ferrite phase form at high temperatures. Therefore, the upper limit of the Mo content can be set to 3.2%, preferably 3.0%, and more preferably 2.8%.

[0051] <Cu: 1.00% or less>

[0052] Cu is an element that has the effect of hardening stainless steel during aging treatment. However, if the Cu content is too high, the hot workability deteriorates, which causes cracking. Therefore, the upper limit of the Cu content can be set to 1.00%, preferably 0.90%, and more preferably 0.80%. On the other hand, the lower limit of the Cu content is not particularly limited, and can be preferably set to 0.01%, more preferably 0.02%, and still more preferably 0.03%.

[0053] <N: 0.03 to 0.15%>

[0054] N is an austenite-forming element. In addition, N is an extremely effective element for hardening the austenite phase and the martensite phase. However, if the N content is excessively high, it causes bubble formation during casting. Therefore, the upper limit of the N content can be set to 0.15%, preferably 0.13%, more preferably 0.12%. On the other hand, from the viewpoint of ensuring the above effects of N, the lower limit of the N content can be set to 0.03%, preferably 0.05%.

[0055] <O: 0.0050% or less>

[0056] If the O content is excessively high, coarse inclusions with an average diameter exceeding 5 μm tend to be easily formed. Therefore, the upper limit of the O content is preferably set to 0.0050%, more preferably 0.0045%, still more preferably 0.0040%. On the other hand, the lower limit of the O content is not particularly limited, but if the O content is excessively low, Mn, Si and the like are less likely to be oxidized, increasing the proportion of Al₂O₃ in the inclusions. Therefore, the lower limit of the O content can be preferably set to 0.0001%, more preferably 0.0010%, still more preferably 0.0020%.

[0057] <Co: 0.05 to 0.50%>

[0058] Co is an element optionally contained in the austenitic stainless steel sheet. Co has the effect of improving crevice corrosion resistance. From the viewpoint of exerting this effect of Co, the lower limit of the Co content can be preferably set to 0.05%, more preferably 0.08%, still more preferably 0.10%. On the other hand, if the Co content is excessively high, the austenitic stainless steel sheet is hardened and the ductility is deteriorated. Therefore, the upper limit of the Co content can be preferably set to 0.50%, more preferably 0.40%, still more preferably 0.30%.

[0059] <Al: 0.15% or less>

[0060] Al is an element optionally contained in the austenitic stainless steel sheet. Al has a higher affinity for oxygen than Si and Mn. If the Al content is excessively high, coarse oxide-based inclusions that serve as starting points for internal cracks tend to be easily formed during cold rolling. Therefore, the upper limit of the Al content can be preferably set to 0.15%, more preferably 0.13%. On the other hand, the lower limit of the Al content is not particularly limited, but excessive reduction of Al leads to an increase in manufacturing cost, so it can be preferably set to 0.01%, more preferably 0.03%, still more preferably 0.05%.

[0061] <V:0.0001~0.5000%>

[0062] V is an element included in austenitic stainless steel sheets as needed. V is an element that enhances age hardening properties during aging treatment. From the viewpoint of fully obtaining this effect, the lower limit of V content can preferably be set at 0.0001%, more preferably at 0.0010%. On the other hand, if the V content is too high, it will lead to an increase in manufacturing costs. Therefore, the upper limit of V content can preferably be set at 0.5000%, more preferably at 0.4800%, and even more preferably at 0.4500%.

[0063] <Ti:0.01~0.50%>

[0064] Ti is an element included in austenitic stainless steel sheets as needed. Ti forms carbonitrides and suppresses the decline in corrosion resistance caused by sensitization by fixing C and N. From the viewpoint of achieving this effect, the lower limit of the Ti content can be preferably set at 0.01%, more preferably at 0.03%, and even more preferably at 0.05%. On the other hand, if the Ti content is too high, the solid solution of C and N decreases, and as carbides, they precipitate unevenly and locally, sometimes hindering the growth of recrystallized grains. Furthermore, Ti is a high-priced metal, leading to increased manufacturing costs. Therefore, the upper limit of the Ti content can be preferably set at 0.50%, more preferably at 0.40%, and even more preferably at 0.30%.

[0065] <B:0.0001~0.0150%>

[0066] Boron (B) is an element included in austenitic stainless steel sheets as needed. Excessive B content may lead to decreased workability due to the formation of borides. Therefore, the upper limit of the B content is preferably set at 0.0150%, more preferably at 0.0100%. On the other hand, the lower limit of the B content is not particularly limited, but it is preferably set at 0.0001%, more preferably at 0.0002%.

[0067] <Nb:0.001~0.100%>

[0068] Nitrogen (Nb) is an element included in austenitic stainless steel sheets as needed. Nb has a high affinity for both carbon (C) and nitrogen (N), and during hot rolling, it precipitates as carbides or nitrides, reducing the amount of dissolved C and N in the parent phase and improving workability. From the viewpoint of achieving this effect, the lower limit of the Nb content is preferably set at 0.001%, more preferably at 0.005%. On the other hand, if the Nb content is too high, the austenitic stainless steel sheet will harden and its ductility will decrease. Therefore, the upper limit of the Nb content is preferably set at 0.100%, more preferably at 0.050%.

[0069] <Mg:0.0001~0.0030%>

[0070] Mg is an element included in austenitic stainless steel sheets as needed. In molten steel, Mg forms Mg oxide with Al, acting as a deoxidizer. From the viewpoint of achieving this function, the lower limit of the Mg content can preferably be set at 0.0001%, more preferably at 0.0005%. On the other hand, if the Mg content is too high, the toughness of the austenitic stainless steel sheet decreases. Therefore, the upper limit of the Mg content can preferably be set at 0.0030%, more preferably at 0.0020%.

[0071] <Ca:0.0003~0.0100%>

[0072] Ca is an element included in austenitic stainless steel sheets as needed. Ca has the effect of improving hot workability. From the viewpoint of maximizing this effect of Ca, the lower limit of the Ca content can be preferably set at 0.0003%, more preferably at 0.0005%. On the other hand, if the Ca content is too high, the toughness of the austenitic stainless steel sheet decreases. Therefore, the upper limit of the Ca content can be preferably set at 0.0100%, more preferably at 0.0050%.

[0073] <Sn:0.001~0.500%>

[0074] Sn is an element included in austenitic stainless steel sheets as needed. Sn has the effect of improving workability by promoting the formation of deformation bands during rolling. From the viewpoint of maximizing this effect of Sn, the lower limit of the Sn content can be preferably set at 0.001%, more preferably at 0.003%. On the other hand, if the Sn content is too high, the effect of Sn will saturate, and workability will decrease. Therefore, the upper limit of the Sn content can be preferably set at 0.500%, more preferably at 0.200%.

[0075] <Pb:0.0001~0.0100%>

[0076] Pb is an element included in austenitic stainless steel sheets as needed. Pb has the effect of improving machinability. From the viewpoint of maximizing this effect of Pb, the lower limit of the Pb content can be preferably set at 0.0001%, more preferably at 0.0005%. On the other hand, if the Pb content is too high, the melting point of the grain boundaries decreases, and the bonding strength of the grain boundaries decreases, raising concerns about deterioration of hot workability due to liquefaction cracks based on grain boundary melting. Therefore, the upper limit of the Pb content can be preferably set at 0.0100%, more preferably at 0.0080%.

[0077] <W:0.0001~0.5000%>

[0078] W is an element included in austenitic stainless steel sheets as needed. W has the effect of improving high-temperature strength without compromising ductility at room temperature. From the viewpoint of maximizing this effect of W, the lower limit of the W content can preferably be set at 0.0001%, more preferably at 0.0005%. On the other hand, if the W content is too high, coarse eutectic carbides are formed, causing a decrease in ductility. Therefore, the upper limit of the W content can preferably be set at 0.5000%, more preferably at 0.4500%.

[0079] <Zr:0.0001~0.1000%>

[0080] Zr is an element included in austenitic stainless steel sheets as needed. Zr has a high affinity for both carbon (C) and nitrogen (N), and during hot rolling, it precipitates as carbides or nitrides, reducing the amount of dissolved C and N in the parent phase and improving workability. From the viewpoint of achieving this effect, the lower limit of the Zr content is preferably set at 0.0001%, more preferably at 0.0005%. On the other hand, if the Zr content is too high, the austenitic stainless steel sheet will harden and its ductility will decrease. Therefore, the upper limit of the Zr content is preferably set at 0.1000%, more preferably at 0.0500%.

[0081] <REM:0.0001~0.3000%>

[0082] REM (refined iron oxide) is an element included in austenitic stainless steel sheets as needed. REM (elements with atomic numbers 21, 39, 57-71, such as La, Ce, and Nd) has the effect of improving resistance to high-temperature oxidation. From the viewpoint of maximizing this effect of REM, the lower limit of REM content can preferably be set at 0.0001%, more preferably at 0.0010%. On the other hand, if the REM content is too high, the effect of REM will be saturated, and surface defects will occur during hot rolling, resulting in decreased manufacturability. Therefore, the upper limit of REM content can preferably be set at 0.3000%, more preferably at 0.1000%, and even more preferably at 0.0500%. REM can be used as a single element or in combination with multiple different elements.

[0083] <Md 30 -30~0℃>

[0084] Md 30 This represents the temperature (°C) at which 50% of the austenitic (γ) single-phase microstructure transforms into martensite when a strain of 0.30 is applied. Therefore, it means that Md... 30 The higher the temperature, the less stable the austenite becomes.

[0085] Md 30 It can be represented by the following formula (1).

[0086] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)

[0088] In the formula, the element symbols represent the content (mass%) of each element.

[0089] If Md 30 If the Md value is too low, the stability of the austenite phase increases, making it difficult to transform the austenite phase into work-induced martensite through cold rolling, thus hindering the achievement of high strength. Therefore, Md... 30 The lower limit is set at -30°C. On the other hand, if Md 30 If the concentration of Md is too high, the austenite phase becomes unstable, and the phase transformation induced by cold rolling increases the amount of martensite. Furthermore, it becomes difficult to control the dislocation density of each phase described below within the desired range, thus failing to obtain the desired ductility and fatigue properties. Therefore, Md... 30 The upper limit is set at 0℃.

[0090] The austenitic stainless steel sheet according to embodiments of the present invention has a metallic structure in which the content of work-induced martensite phase is 30.0% by volume or more. By controlling the content of work-induced martensite phase within such a range, the strength and fatigue properties of the austenitic stainless steel sheet can be improved. Furthermore, from the viewpoint of consistently obtaining this effect, the content of work-induced martensite phase is preferably 30.5% by volume or more, more preferably 31.0% by volume or more. Moreover, there is no particular limitation on the upper limit of the content of work-induced martensite phase, but it is preferably 70.0% by volume, more preferably 65.0% by volume.

[0091] The content of processing-induced martensite can be determined using methods known in this technical field. For example, the content of processing-induced martensite can be determined using a ferrite content analyzer (FeritScope).

[0092] In embodiments of the present invention, the austenitic stainless steel sheet preferably has an average grain size of 15.0 μm or less. By controlling the average grain size within such a range, it is easy to improve the strength and fatigue properties of the austenitic stainless steel sheet. From the viewpoint of consistently achieving this effect, the average grain size is more preferably 12.0 μm or less, and even more preferably 10.0 μm or less. Furthermore, there is no particular limitation on the lower limit of the average grain size, but it is preferably 1.0 μm, and more preferably 3.0 μm.

[0093] The average crystal grain size can be determined according to JIS G0551:2020.

[0094] In embodiments of the present invention, the austenitic stainless steel plate preferably has a residual austenite phase dislocation density of 0.40 × 10⁻⁶. 16 m -2 The above demonstrates how controlling the dislocation density of the retained austenite phase within a specific range can stably improve the strength and fatigue strength of austenitic stainless steel plates. Conversely, when the dislocation density of the retained austenite phase is below 0.40 × 10⁻⁶, the strength and fatigue strength of the stainless steel plate can be significantly increased. 16 m -2 At times, dislocation movement within the phase cannot be sufficiently suppressed, sometimes leading to a decrease in strength and fatigue strength. Furthermore, while there is no particular upper limit to the dislocation density of the retained austenite phase, it is preferably 5.0 × 10⁻⁶. 16 m -2 More preferably 3.0×10 16 m -2 Further preferred is 2.0×10 16 m -2 .

[0095] The term "dislocation density" refers to the total length of dislocations contained in a unit volume of crystal. Typically, during cold rolling, some of the moving dislocations accumulate in the material, thus increasing the dislocation density. These accumulated dislocations interact with subsequent dislocations, hindering their movement. Therefore, an increase in dislocation density improves strength and fatigue properties.

[0096] Furthermore, the dislocation density of the retained austenite phase can be calculated by line profile analysis of the shape of the diffraction peaks measured by X-ray diffraction.

[0097] The austenitic stainless steel sheet of the present invention can contain inclusions with an average diameter of 1.5 μm or less. Large inclusions may cause a decrease in the strength and fatigue strength of the austenitic stainless steel sheet, but fine inclusions with an average diameter of 1.5 μm or less can suppress the influence on the strength and fatigue strength of the austenitic stainless steel sheet.

[0098] The term "inclusions" refers to non-metallic compounds such as oxides or sulfides.

[0099] The inclusions in the austenitic stainless steel sheet according to the embodiments of the present invention are preferably 1000 inclusions / mm. 2 The following points illustrate how controlling the number of inclusions within a certain range can easily and consistently improve the strength and fatigue strength of austenitic stainless steel sheets. From the viewpoint of consistently achieving this effect, a more preferable number of inclusions is 980 inclusions / mm². 2 The following is a further preferred value: 960 pieces / mm 2 Furthermore, since the number of inclusions is preferably small, there is no particular limitation on the lower limit of the number of inclusions.

[0100] The number of inclusions can be determined using the point counting method based on JIS G0555:2020.

[0101] The tensile strength (TS) of the austenitic stainless steel sheet according to embodiments of the present invention is preferably 2200 MPa or more, more preferably 2250 MPa or more. By controlling the tensile strength within such a range, the strength of the austenitic stainless steel sheet can be ensured. Furthermore, there is no particular limitation on the upper limit of the tensile strength, which is generally 3000 MPa, and preferably 2500 MPa.

[0102] The tensile strength of austenitic stainless steel plates can be determined according to JIS Z2241:2011.

[0103] The tensile strength (EL) at break of the austenitic stainless steel sheet according to embodiments of the present invention is preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5%. By controlling the tensile strength at break within such a range, the ductility of the austenitic stainless steel sheet can be ensured. Furthermore, there is no particular limitation on the upper limit of the tensile strength at break, which is generally 10.0%, and preferably 5.0%.

[0104] The tensile strength at break of austenitic stainless steel plates can be determined according to JIS Z2241:2011.

[0105] The austenitic stainless steel sheet of the embodiments of the present invention preferably has a flexural endurance of 1100 cycles or more, more preferably 1120 cycles or more, and even more preferably 1130 cycles or more, as measured according to JIS P8115:2001. A flexural endurance within this range indicates excellent fatigue strength of the austenitic stainless steel sheet. Furthermore, the higher the flexural endurance, the better the fatigue strength; therefore, there is no particular upper limit.

[0106] The number of folding cycles, as described above, can be measured according to JIS P8115:2001.

[0107] The thickness of the austenitic stainless steel sheet in the embodiments of the present invention is 0.15 mm or less, preferably 0.12 mm or less, more preferably 0.10 mm or less, and even more preferably 0.08 mm or less. By specifying such a thickness, it is possible to achieve thin-walled and lightweight construction for various components. Furthermore, the lower limit of the thickness can be adjusted according to the application and is not particularly limited, but is generally 0.01 mm.

[0108] The manufacturing method of the austenitic stainless steel sheet according to embodiments of the present invention is not particularly limited as long as it is a method capable of forming an austenitic stainless steel sheet with the above-described characteristics. For example, a typical manufacturing method of the austenitic stainless steel sheet according to embodiments of the present invention includes an intermediate rolling annealing process, a quenching and tempering rolling process, and an aging treatment process.

[0109] The intermediate rolling annealing process involves repeatedly performing cold rolling and annealing steps on a hot-rolled annealed sheet with the above composition two or more times. By performing the intermediate rolling annealing process, the processing-induced martensite phase is generated and then undergoes a reverse phase transformation, thereby refining the grain size and increasing the strength.

[0110] Hot-rolled annealed steel sheets can be manufactured using the following method: smelting stainless steel with the above-mentioned composition, followed by forging or casting, then hot rolling, and finally annealing. The conditions for hot rolling and annealing can be adjusted appropriately according to the composition of the stainless steel and are not particularly limited. Furthermore, pickling or other treatments can be performed as needed after annealing.

[0111] The steps of cold rolling and annealing can be repeated more than twice. For example, when performing this step three times, it can be done in the order of cold rolling-annealing-cold rolling-annealing-cold rolling-annealing. Therefore, even if the number of times this step is increased, it will still start with cold rolling and end with annealing. There is no particular limit to the number of times this step can be performed, but it is generally 10 times, preferably 5 times.

[0112] The cold rolling conditions in each step can be adjusted appropriately according to the composition of the stainless steel, and there are no particular limitations. However, for cold rolling of two or more times, the rolling rate is preferably 50% or more, more preferably 55% or more, and even more preferably 60% or more. By controlling the rolling rate within such a range, it becomes easier to refine the grain size. Furthermore, there are no particular limitations on the upper limit of the rolling rate, for example, it can be 80% or 90%.

[0113] The annealing conditions in each step are similar and can be adjusted appropriately according to the composition of the stainless steel; there are no particular limitations. However, the annealing temperature is preferably 900°C or higher, more preferably 950°C or higher, and even more preferably 1000°C or higher. By controlling the temperature within such a range, it becomes easier to refine the grain size. Furthermore, the annealing temperatures in each step can be the same or different. Moreover, there are no particular limitations on the upper limit of each annealing temperature; for example, it can be 1200°C or 1300°C.

[0114] In addition, the annealing time can be adjusted appropriately according to the annealing temperature, for example, from 10 to 300 seconds.

[0115] The quenching and tempering rolling process involves quenching and tempering the cold-rolled annealed sheet obtained from the intermediate rolling and annealing process at a rolling rate of over 60%, thereby adjusting the thickness to below 0.15 mm. By performing the quenching and tempering rolling process, strain can be accumulated in the austenitic phase while ensuring a certain amount of processing-induced martensite phase is generated, thus increasing the strength.

[0116] From the viewpoint of consistently achieving the aforementioned effects, the rolling ratio for quenching and tempering is preferably 62% or more, more preferably 65% ​​or more. There is no particular upper limit to this rolling ratio; for example, it may be 80% or 90%.

[0117] The aging process is a process of aging the quenched and tempered rolled plate obtained in the quenching and tempering rolling process under specified conditions. The aging process can be carried out under the condition that the B value is 11500 to 15000, as expressed by the following formula (2). By aging under such conditions, the strength can be improved by precipitation hardening based on the austenitic phase (γ phase).

[0118] B = T(logt + 20) (2)

[0119] (In the formula, T is temperature (K) and t is time (h))

[0120] Regarding the B value, from the viewpoint of consistently achieving the aforementioned effects, a value of 12000–14800 is preferred, more preferably 12500–14500, and even more preferably 13000–14000. Furthermore, the temperature and time of the aging treatment are not particularly limited as long as the above conditions are met, but typical temperatures are 300–700°C, and typical times are 5–500 seconds.

[0121] The austenitic stainless steel sheet of the embodiments of the present invention has high strength and excellent fatigue characteristics. Therefore, it can be used for various components requiring thin walls and lightweight construction, such as structural and functional components in communication devices like smartphones and precision equipment like personal computers. In particular, the austenitic stainless steel sheet of the embodiments of the present invention is suitable for use as a leaf spring for the back plate supporting the bending function of the liquid crystal display screen in foldable smartphones and the like.

[0122] Example

[0123] The present invention will now be described in detail by way of examples, but this is not to be construed as limiting the invention to these examples.

[0124] 30 kg of stainless steel with the composition shown in Table 1 was melted under vacuum and cast into a 30 mm thick plate. This plate was then heated at 1230°C for 2 hours and hot-rolled to obtain a hot-rolled plate with the thickness shown in Table 2. Next, the hot-rolled plate was annealed and pickled to form a hot-rolled annealed plate. This annealed plate was then subjected to intermediate rolling annealing, tempering rolling, and aging treatment processes sequentially to obtain an austenitic stainless steel plate. The conditions for the intermediate rolling annealing, tempering rolling, and aging treatment processes are shown in Table 2. Furthermore, the annealing conditions in the intermediate rolling annealing process were set to 1050°C for 60 seconds.

[0125] Table 1

[0126]

[0127] Table 2

[0128]

[0129] The austenitic stainless steel sheets obtained according to the above were evaluated as follows.

[0130] <Average crystal grain size>

[0131] The average grain size was determined by a comparative method based on JIS G0551:2020. The observation surface of the average grain size was obtained by electrolytic polishing of the surface of austenitic stainless steel plate, followed by etching with aqua regia after mirror polishing.

[0132] <Content of processing-induced martensite phase>

[0133] Test pieces were cut from austenitic stainless steel plates, and the content of work-induced martensite was determined using a ferrite content analyzer (Fischer FERITESCOPE MP30E-S). Measurements were taken at any three points on the surface of the test piece, and the average value was taken as the result. Furthermore, the work-induced martensite phase will sometimes be abbreviated as "M phase" below.

[0134] <Dislocation density of the retained austenite phase>

[0135] The dislocation density of the retained austenite phase is calculated by line profile analysis of the diffraction peaks measured using X-ray diffraction. In the microstructure with dislocations introduced, lattice distortion occurs centered on the dislocations, and the arrangement of dislocations further develops small-angle grain boundaries and unit cell structures. By capturing these details with X-rays, the dislocation density can be calculated.

[0136] Regarding the test pieces, samples were cut from austenitic stainless steel plates at arbitrary locations and used after mechanical and chemical grinding.

[0137] The surface microstructure of the test piece was subjected to X-ray diffraction, and the dislocation density ρ was calculated from the single diffraction peak of {111} in the retained austenite phase. The following equation (3) was used in the calculation of the dislocation density ρ.

[0138] ρ=[3(2π) 1 / 2 <ε 2 > 1 / 2 ] / Db (3)

[0139] In the formula, <ε 2 > represents the root mean square strain, D represents the crystallite size, and b represents the Burgers vector.

[0140] Furthermore, the root mean square strain <ε used in equation (3) 2 > and the crystallite size D is obtained by the following formula (4).

[0141] -lnA(L) / L=1 / D+[-1 / (2D 2 )+2π 2 <ε 2 h0 2 / a 2 L (4)

[0142] In the formula, lnA(L) is the logarithm of the Fourier coefficients of the line profile of each diffraction peak, L is the Fourier length, and h0 is the line profile of each peak. 2 =h 2 +k 2 +l 2 (The crystal plane indices of the diffraction peaks used by h, k, and l), and a is the lattice constant. Set the vertical axis to -lnA(L) / L and the horizontal axis to L. Calculate D from the y-intercept 1 / D of the graph, and from the slope [-1 / (2D)]... 2 )+2π 2 <ε 2 h0 2 / a 2 Find <ε 2 >

[0143] Furthermore, an X-ray diffraction apparatus (manufactured by Rigaku Corporation) was used as the analytical device, and Cu dry balls were used as the target material. Also, hereafter, the retained austenite phase will sometimes be abbreviated as "γ phase".

[0144] <Average diameter and number of inclusions>

[0145] The average diameter and number of inclusions were determined using a point algorithm based on JIS G0555:2020. The observation surface of the inclusions was obtained by electrolytic polishing of the surface of an austenitic stainless steel plate to achieve a mirror finish.

[0146] <Tensile Strength (TS) and Elongation at Break (EL)>

[0147] JIS 13B test pieces were cut from austenitic stainless steel plates and tested according to JIS Z2241:2011.

[0148] <Number of folding resistance>

[0149] The flexural endurance was determined according to JIS P8115:2001. In the determination of flexural endurance, a test piece measuring 15mm (width direction) × 130mm (rolling direction) was used, and the test was conducted under the following conditions.

[0150] Load: 0.25 kgf

[0151] Test speed: 175 cpm

[0152] Bending angle: 135°

[0153] The radius (R) of the bending pressure plate is 2.0mm.

[0154] The opening of the bending pressure plate is 0.25mm.

[0155] The evaluation results mentioned above are shown in Table 3.

[0156] Table 3

[0157]

[0158] As shown in Table 3, it can be seen that the austenitic stainless steel plates of Examples 1 to 11 have high strength due to their high tensile strength (TS), elongation at break (EL), and flexural strength, and have excellent fatigue characteristics.

[0159] In contrast, the austenitic stainless steel sheet of Comparative Example 1 had too little Si and Mo content and too much Cr content, which resulted in excessive Md content. 30 The value becomes excessively high. As a result, TS, EL, and folding endurance decrease.

[0160] The austenitic stainless steel sheet in Comparative Example 2 had excessively high Si and Cu content, which resulted in excessive Md content. 30 The value becomes too small. As a result, TS (transformation resistance) and folding endurance decrease.

[0161] The austenitic stainless steel sheets in Comparative Examples 3 and 4 have increased thickness and average grain size due to fewer intermediate rolling and annealing processes. As a result, total thickness (TS) and bending resistance decrease.

[0162] In Comparative Example 5, the austenitic stainless steel sheet had a lower TS due to the B value being too small during the aging process.

[0163] In Comparative Example 6, the austenitic stainless steel sheet had an excessively high B value during the aging process, which reduced the dislocation density of the γ phase. As a result, the total tracere (TS) decreased.

[0164] In Comparative Example 7, the austenitic stainless steel sheet had a lower rolling rate during the quenching and tempering process, resulting in a decrease in the content of the M phase and the dislocation density of the γ phase. Consequently, the total saturation (TS) decreased.

[0165] The austenitic stainless steel sheet in Comparative Example 8 had an excessive amount of oxygen, resulting in an increased number of inclusions. Consequently, its flexural strength decreased.

[0166] The results above show that, according to the present invention, even with reduced thickness, it is possible to provide austenitic stainless steel plates with high strength and excellent fatigue properties, as well as a method for manufacturing the same.

[0167] Furthermore, according to the present invention, even with reduced thickness, high-strength and long-life leaf springs can be provided.

[0168] Furthermore, based on the above results, the present invention can be defined as follows.

[0169] [1] An austenitic stainless steel plate, having, by mass, the following composition: C: 0.04–0.11%, Si: 2.0–3.5%, Mn: less than 1.50%, Ni: 6.0–10.0%, Cr: 12.0–15.0%, Mo: 1.3–3.2%, Cu: less than 1.00%, N: 0.03–0.15%, O: less than 0.0050%, the remainder being Fe and impurities, and Md expressed by the following formula (1). 30 The value is -30 to 0℃.

[0170] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)

[0172] (In the formula, the element symbols represent the content (mass%) of each element.)

[0173] Among them, the metal microstructure has a processing-induced martensite phase content of 30.0% or more, and

[0174] The thickness is less than 0.15mm.

[0175] [2] The austenitic stainless steel sheet according to [1] above, wherein, based on mass, it further contains one or more of the following: Co: 0.05-0.50%, Al: less than 0.15%, V: 0.0001-0.5000%, Ti: 0.01-0.50%, B: 0.0001-0.0150%, Nb: 0.001-0.100%, Mg: 0.0001-0.0030%, Ca: 0.0003-0.0100%, Sn: 0.001-0.500%, Pb: 0.0001-0.0100%, W: 0.0001-0.5000%, Zr: 0.0001-0.1000%, and REM: 0.0001-0.3000%.

[0176] [3] The austenitic stainless steel plate according to [1] or [2] above, wherein the average crystal grain size is less than 15.0 μm.

[0177] [4] The austenitic stainless steel plate according to any one of [1] to [3] above, wherein the dislocation density of the retained austenite phase is 0.40 × 10⁻⁶. 16 m -2 above.

[0178] [5] The austenitic stainless steel sheet according to any one of [1] to [4] above, wherein it contains inclusions with an average diameter of 1.5 μm or less.

[0179] [6] According to the austenitic stainless steel plate described in [5] above, wherein the inclusions are 1000 per mm. 2 the following.

[0180] [7] The austenitic stainless steel plate according to any one of [1] to [6] above, wherein the tensile strength (TS) is 2200 MPa or more.

[0181] [8] The austenitic stainless steel sheet according to any one of [1] to [7] above, wherein the tensile strength at break (EL) is 0.5% or more.

[0182] [9] The austenitic stainless steel sheet according to any one of [1] to [8] above, wherein the number of flexural cycles measured according to JIS P8115:2001 is more than 1100.

[0183]

[10] A method for manufacturing an austenitic stainless steel plate, comprising the following steps:

[0184] The intermediate rolling annealing process involves sequentially cold rolling and annealing the hot-rolled annealed sheet, and repeating this step more than twice. The composition of the hot-rolled annealed sheet, based on mass, contains C: 0.04-0.11%, Si: 2.0-3.5%, Mn: less than 1.50%, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: less than 1.00%, N: 0.03-0.15%, O: less than 0.0050%, with the remainder containing Fe and impurities. Md is expressed by the following formula (1). 30 The value is -30 to 0℃;

[0185] Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1)

[0187] (In the formula, the element symbols represent the content (mass%) of each element.)

[0188] The temper rolling process involves temper rolling the cold-rolled annealed sheet obtained from the intermediate rolling annealing process at a rolling rate of 60% or more, thereby adjusting the thickness to below 0.15 mm; and

[0189] The aging process involves aging the tempered rolled plate obtained from the tempering rolling process according to the following formula (2), where the B value is between 11500 and 15000.

[0190] B = T(logt + 20) (2)

[0191] (In the formula, T is temperature (K) and t is time (h))

[0192]

[11] According to the manufacturing method of the austenitic stainless steel plate described in

[10] above, wherein the hot-rolled annealed plate further contains, by weight, one or more of the following: Co: 0.05-0.50%, Al: less than 0.15%, V: 0.0001-0.5000%, Ti: 0.01-0.50%, B: 0.0001-0.0150%, Nb: 0.001-0.100%, Mg: 0.0001-0.0030%, Ca: 0.0003-0.0100%, Sn: 0.001-0.500%, Pb: 0.0001-0.0100%, W: 0.0001-0.5000%, Zr: 0.0001-0.1000%, and REM: 0.0001-0.3000%.

[0193]

[12] In the method for manufacturing austenitic stainless steel sheet according to

[10] or

[11] above, the rolling rate of each of the two or more cold rolling processes in the intermediate rolling annealing process is 50% or more.

[0194]

[13] The method for manufacturing austenitic stainless steel sheet according to any one of

[10] to

[12] above, wherein the aging time in the aging treatment process is 5 to 500 seconds.

[0195]

[14] A leaf spring comprising an austenitic stainless steel plate as described in any one of [1] to [9] above.

Claims

1. An austenitic stainless steel plate, comprising, by weight, C: 0.04–0.11%, Si: 2.0–3.5%, Mn: less than 1.50%, Ni: 6.0–10.0%, Cr: 12.0–15.0%, Mo: 1.3–3.2%, Cu: less than 1.00%, N: 0.03–0.15%, O: less than 0.0050%, the remainder being Fe and impurities, and Md expressed by the following formula (1). 30 The value is -30 to 0℃. Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1) In the formula, the element symbols represent the content of each element in terms of mass%. in, It has a metallic microstructure with a processing-induced martensite phase content of 30.0% by volume or more, and, Thickness less than 0.15mm, The tensile strength TS is above 2200MPa. The average crystal grain size is below 15.0 μm.

2. The austenitic stainless steel plate according to claim 1, wherein, Based on mass, it further contains one or more elements selected from Co: 0.05-0.50%, Al: less than 0.15%, V: 0.0001-0.5000%, Ti: 0.01-0.50%, B: 0.0001-0.0150%, Nb: 0.001-0.100%, Mg: 0.0001-0.0030%, Ca: 0.0003-0.0100%, Sn: 0.001-0.500%, Pb: 0.0001-0.0100%, W: 0.0001-0.5000%, Zr: 0.0001-0.1000%, and REM: 0.0001-0.3000%.

3. The austenitic stainless steel plate according to claim 1 or 2, wherein, The dislocation density of the retained austenite phase is 0.40 × 10⁻⁶. 16 m -2 above.

4. The austenitic stainless steel plate according to claim 1 or 2, wherein, It contains inclusions with an average diameter of less than 1.5 μm.

5. The austenitic stainless steel plate according to claim 4, wherein, The inclusions are 1000 per mm. 2 the following.

6. The austenitic stainless steel plate according to claim 1 or 2, wherein, The tensile strength at break (EL) is above 0.5%.

7. The austenitic stainless steel plate according to claim 1 or 2, wherein, The flexural endurance, as measured by JIS P8115:2001, is over 1100 cycles.

8. A method for manufacturing an austenitic stainless steel plate, wherein, It includes the following processes: The intermediate rolling annealing process involves sequentially cold rolling and annealing the hot-rolled annealed sheet, and repeating this step more than twice. The composition of the hot-rolled annealed sheet, based on mass, contains C: 0.04-0.11%, Si: 2.0-3.5%, Mn: less than 1.50%, Ni: 6.0-10.0%, Cr: 12.0-15.0%, Mo: 1.3-3.2%, Cu: less than 1.00%, N: 0.03-0.15%, O: less than 0.0050%, with the remainder containing Fe and impurities. Md is expressed by the following formula (1). 30 The value is -30 to 0℃. Md 30 =551-462(C+N)-9.2Si-8.1Mn-29(Ni+Cu)-13.7Cr-18.5Mo (1) In the formula, the element symbol represents the content of each element in terms of mass%. The temper rolling process involves temper rolling the cold-rolled annealed sheet obtained from the intermediate rolling annealing process at a rolling rate of 60% or more, thereby adjusting the thickness to below 0.15 mm; and The aging process involves aging the tempered rolled plate obtained from the tempering rolling process under conditions where the B value is between 11500 and 15000, as shown in the following formula (2). B = T(logt + 20) (2) In the formula, T is the temperature in K, and t is the time in hours.

9. The method for manufacturing austenitic stainless steel plate according to claim 8, wherein, The hot-rolled annealed plate, based on mass, further contains one or more elements selected from the following: Co: 0.05-0.50%, Al: less than 0.15%, V: 0.0001-0.5000%, Ti: 0.01-0.50%, B: 0.0001-0.0150%, Nb: 0.001-0.100%, Mg: 0.0001-0.0030%, Ca: 0.0003-0.0100%, Sn: 0.001-0.500%, Pb: 0.0001-0.0100%, W: 0.0001-0.5000%, Zr: 0.0001-0.1000%, and REM: 0.0001-0.3000%.

10. The method for manufacturing austenitic stainless steel sheet according to claim 8 or 9, wherein, The rolling rate of each of the two or more cold rolling processes in the intermediate rolling annealing process is 50% or more.

11. The method for manufacturing austenitic stainless steel sheet according to claim 8 or 9, wherein, The aging time in the aging process is 5 to 500 seconds.

12. A leaf spring comprising an austenitic stainless steel plate as described in claim 1 or 2.

Citation Information

Patent Citations

  • Motor vehicle with front wheel drive

    CA300100A

  • Production of high strength austenitic stainless steel excellent in toughness

    JP1995090372A

  • High strength austenitic stainless steel plate for flapper valve, excellent in fatigue characteristic, and its production

    JP1998140294A

  • Austenitic stainless steel material, method for producing same, and plate spring

    WO2021230244A1